Urinary Concentrations of Phthalate Metabolites and Pregnancy Loss Among Women Conceiving with Medically Assisted Reproduction. Issue 6 (November 2016) - Messerlian, Carmen; Wylie, Blair J.; Mínguez-Alarcón, Lidia; Williams, Paige L.; Ford, Jennifer B.; Souter, Irene C.; Calafat, Antonia M.; Hauser, Russ
Abstract : Background: Animal studies demonstrate that several phthalates are embryofetotoxic and are associated with increased pregnancy loss and malformations. Results from human studies on phthalates and pregnancy loss are inconsistent. Methods: We examined pregnancy loss prospectively in relation to urinary phthalate metabolite concentrations among women undergoing medically assisted reproduction. We used data from 256 women conceiving 303 pregnancies recruited between 2004 and 2012 from the Massachusetts General Hospital Fertility Center. We quantified 11 phthalate metabolite concentrations and calculated the molar sum of four di(2-ethylhexyl) phthalate (DEHP) metabolites (ΣDEHP). We estimated risk ratios (RRs) and 95% confidence intervals for biochemical loss and total pregnancy loss (<20 weeks' gestation) across quartiles using repeated measures log-binomial models, adjusted for age, body mass index, smoking and infertility diagnosis. Results: Of the 303 pregnancies, 83 (27%) ended in loss less than 20 weeks' gestation and among these, 31 (10%) ended in biochemical loss. Although imprecise, the RRs for biochemical loss increased across quartiles of ΣDEHP and three individual DEHP metabolites. For ΣDEHP, the RRs (confidence intervals) were 2.3 (0.63, 8.5), 2.0 (0.58, 7.2), and 3.4 (0.97, 11.7) for quartiles two, three, and four, compared with one, respectively ( P trend = 0.04). RRs for total pregnancy loss were elevated in the highest quartiles of ΣDEHP and three DEHP metabolites. The remaining seven phthalate metabolite concentrations evaluated were not associated with either outcome. Conclusions: We found a suggestive pattern of association between conception cycle-specific urinary concentrations of DEHP metabolites and biochemical and total pregnancy loss among women undergoing medically assisted reproduction.